Seedling survival under drought differs between an annual (Hordeum vulgare) and a perennial grass (Dactylis glomerata) - Volaire, Florence (The New phytologist, 2003)
•  In semiarid areas, populations of cereal crop plants can be reduced by severe drought occurring during the vegetative stage, leading to subsequent serious yield reduction. This study aimed to analyse and compare survival and dehydration tolerance in two contrasting barley (Hordeum vulgare) cultivars (cvs) and in a drought resistant perennial grass, cocksfoot (Dactylis glomerata). •  In pot experiments, seedlings were subjected to intensifying droughts for analysis of adaptive responses and survival following a range of final soil water potentials (SWP). •  Survival rates were 100% in cocksfoot and 32% in the drought resistant barley cv. Tadmor at a SWP of -2.5 MPa. In cocksfoot, lamina water potentials decreased earlier and water content in enclosed leaf bases stabilized at low SWP. This strategy of dehydration tolerance was associated with high survival. •  At moderate water deficit, barley cv. Tadmor exhibited a 5-fold greater osmotic adjustment in lamina, lower senescence and higher accumulation of dehydrins in enclosed leaf bases than the drought sensitive cv. Plaisant. However, under severe drought, water content in enclosed leaf bases declined constantly and was associated with similar mortality in both cvs. Dehydration tolerance was low in barley and not correlated with dehydrin accumulation or resistance to moderate drought